LncRNA RBAT1 reduces chemosensitivity of cancer cells to carboplatin/paclitaxel by sponging miR‑27b in endometrial carcinoma - Lingye Fan; Chunyan Wang; Ping Zhan; Yaofang Liu (BMC, 2023)
Abstract Background A recent study reported the role of long non-coding RNA (lncRNA) RBAT1 in promoting the development of retinoblastoma and bladder cancer. However, its function in other cancers is unclear. We then studied the role of RBAT1 in endometrial carcinoma (EC). Methods The expression of RBAT1 and miR-27b in EC and paired non-tumor samples from advanced EC patients, as well as in plasma samples of EC patients and healthy controls were detected by RT-qPCR. The direct interaction between RBAT1 and miR-27b, and the subcellular location of RBAT1 were determined by RNA-RNA pulldown assay and subcellular fractionation assay, respectively. Results EC tissues showed increased expression levels of RBAT1 and decreased expression levels of miR-27b compared to that in non-tumor tissues. Moreover, EC patients showed higher plasma expression levels of RBAT1 and lower plasma expression levels of miR-27b compared to that in the controls. Drug-resistant (DR) patients showed higher expression levels of RBAT1 and lower expression levels of miR-27b in both EC tissues and plasma samples. RBAT1 was detected in both nuclear and cytoplasm and it directly interacted with miR-27b. RBAT1 and miR-27b did not affect the expression of each other. Upregulation of RBAT1 promoted the expression of multidrug-resistant-related protein (P-gp, MRP1, and BCRP). Overexpression of RBAT1 and inhibition of miR-27b promoted cell viability and impeded cell apoptosis and cell cycle arrest at G0-G1 phase, while knockdown of RBAT1 and overexpression of miR-27b inhibited cell viability and induced cell apoptosis and cell cycle arrest at G0-G1 phase. Moreover, miR-27b could abolish RBAT1-induced effects on cell viability, apoptosis and cell cycle. Conclusion RBAT1 may reduce the chemosensitivity of EC cells to carboplatin/paclitaxel by sponging miR-27b in EC.